CLASSROOM INTERACTION: A CASE STUDY OF STUDENT TALK IN AN EFL CLASSROOM - Karmila, Debi (2015)
Classroom Interaction: A Case Study of Student Talk in an EFL Classroom This research aimed to identify the role of student talk which appeared the most in classroom interaction using Learner Language Exchange Aspect Analysis proposed by Suherdi (2010) and added by Berry (1981) and Ventola (1988); and to investigate the factors influencing the role. The research employed qualitative case study method. The research utilized three instruments; classroom observation, note-taking, and interview. The research was taken place in a class comprising six students in a private course. The research findings showed that the most-appeared role was category 1 (receiving-reacting-verbally-answering-satisfying). Meanwhile, the factors influencing category 1 to appear the most were the way the teacher manages the classroom, the size of the class, student linguistic abilities, and topic area. Key words: classroom interaction, classroom discourse analysis, student talk Interaksi Kelas: Sebuah Studi Kasus Tuturan Siswa di sebuah Kelas Bahasa Inggris sebagai Bahasa Asing (EFL) Penelitian ini bertujuan untuk mengidentifikasi peran tuturan siswa yang muncul paling banyak dalam interaksi kelas menggunakan Learner Language Exchange Analysis yang diusulkan oleh Suherdi (2010) dengan ditambah oleh Berry (1981) dan Ventola (1988); dan untuk menginvestigasi faktor-faktor yang mempengaruhi peran tuturan tersebut. Penelitian ini menggunakan metode studi kasus kualitatif. Penelitian ini menggunakan tiga instrumen; observasi kelas, catatan lapangan, dan interview. Penelitian ini dilakukan di sebuah kelas yang terdiri dari enam siswa di sebuah kursus bahasa Inggris. Hasil penelitian menunjukkan bahwa peran tuturan yang paling banyak muncul adalah kategori 1 (menerima-bereaksi-verbal-menjawab-memuaskan). Sementara itu, faktor-faktor yang memengaruhi kategori 1 menjadi peran tuturan yang paling sering muncul adalah cara guru mengatur kelas, ukuran kelas, kemampuan linguistik siswa, dan topik pembelajaran. Kata kunci: interaksi kelas, analisis wacana kelas, tuturan siswa